Radiological Features Of Pre-Eclampsia And Its Complications (Journal of Pharmaceutical Negative Results, 2023)
Background: Pre-eclampsia, a human-pregnancy-specific disease defined as the occurrence of hypertension and significant proteinuria in a previously healthy woman on or after the 20th week of gestation, occurs in about 2–8% of pregnancies . It is the most common medical complication of pregnancy whose incidence has continued to increase worldwide, and It is associated with significant maternal morbidity and mortality, The diagnosis can still be made in the absence of proteinuria if the new-onset hypertension is accompanied by specific signs or symptoms of significant end-organ dysfunction.Doppler interrogation of the uterine artery typically demonstrates low end-diastolic velocity and an early diastolic notch .While in the second trimester there is decrease in the uterine artery vascular resistance represented by increased diastolic blood flow velocity and loss of the early diastolic notch by 22 weeks of gestation Elastography is the set of techniques by which tissue stiffness is estimated as a physical property termed the Young’s modulus (E).the basis of elastography imaging depends on the deformation of the target lesion compared to the background tissue. As softer tissue deform to a greater degree when compressed and therefore show greater or higher strain compared to the background tissue In the first trimster of the normal pregnanacy.